Interoperability of monitoring-related tools - Funika, Włodzimierz; Janik, Arkadiusz (My University, 2005)
Networking, distributed and grid computing have become the commonly used paradigms of programming. Due to the complicated nature of distributed and grid systems and the increasing complexity of the applications designed for these architectures, the development process needs to be supported by different kinds of tools at every stage of a development process. In order to avoid improper influences of one tool to another these tools must cooperate. The cooperation ability is called interoperability. Tools can interoperate on different levels, from exchanging the data in common format, to a semantical level by executing some action as a result of an event in another tool. In this paper we present some interoperability models, with focus on their advantages and major problems due to their use. We also present an interoperability model designed and used in the JINEXT extension to OMIS specification, intended to provide interoperability for OMIS-compliant tools.

Przetwarzanie rozproszone i gridowe jest obecnie dominującym paradygmatem obliczeniowym. Skomplikowany charakter systemów rozproszonych i gridowych oraz rosnąca złożoność projektowanych aplikacji sprawia, że na każdym etapie tworzenia systemu informatycznego konieczne staje się użycie narzędzi wspierających ten proces. Aby uniknąć zakłócenia pracy jednego narzędzia przez prace innego, narzędzia te muszą współpracować. Zdolność ta nazywana jest interoperabilnością. Interoperabilność można rozpatrywać na kilku poziomach, począwszy od wspólnego formatu danych, a skończywszy na poziomie semantycznym, na którym jedno z narzędzi reaguje wykonaniem pewnej akcji w odpowiedzi na zdarzenie wygenerowane przez inne z narzędzi. W artykule przedstawiono kilka modeli interoperabilności, opisując zalety i wady każdego z nich. Przedstawiono równiez model zastosowany w JINEXT, rozszerzeniu specyfikacji OMIS o mechanizm interoperabilności.
Interoperabilność narzędzi monitorujących
Computer Science
Keywords: interoperability; JINEXT; interoperabilność; mediator; JINEXT; mediator; monitoring tools; narzędzia; system monitorujący; OMIS; OMIS